Pengaruh Konsep Diri dan Mata Kuliah Kewirausahaan Terhadap Minat Menjadi Enterpreneur Pada Mahasiswa Semester VII STMIK Budi Darma - Andayanny Andayanny (Politeknik Kutaraja, 2020)
This study aims to see how Self Concepts and Entrepreneurship courses affect students' interest in entrepreneurship among students of semester VII STMIK Budi Darma with a sample of 25 people and by using SPSS 20.00 obtained the results of the regression equation Y = 5.776 + 0.177 X1 + 0.714X2 + e. This shows that the Entrepreneurship Subject Variable is the most influential variable on the interest of STMIK Budi Darma students to become entrepreneurs.